A Comparative Study of Prediction Techniques for Supersonic Missile Aerodynamic Coefficients / Loai A. El-Mahdy … [et al.] - El-Mahdy, Loai A.; Ahmed, Mahmoud Y. M.; Mahmoud, Osama K.; Abdel-Hameed, Omar E. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Evaluating the aerodynamic coefficients of flying vehicles such as missiles is a key step in their design and development procedures. In practice, the aerodynamic coefficients can be estimated using experimental measurements, numerical simulations, or using empirical and semi-empirical engineering tools. In the present paper, these three approaches are compared in the context of examining the aerodynamic coefficients of a fin-stabilized tactical missile. Supersonic flight conditions up to Mach 4 at incidence up to 18 degrees are considered. Lift and drag coefficients as well as the centre of pressure locations based on the three approaches are compared. The flow features around the missile are explored based on the numerical simulations.